Analisis Pengaruh Kepemilikan Institusional Dan Profitabilitas Terhadap Cash Holding Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Terindeks Lq45 Di Bursa Efek Indonesia - Ainul Ridha; Dhian Wahyuni; Dewi Maya Sari (Jurnal Manajemen dan Keuangan, 2019)
This research is aimed to test the effect of institutional ownership and profitability on cash holding with a firm size as moderate variable in LQ45 indexed companies in Indonesia Stock Exchange from 2015 to 2017. Technique of sampling is applied with purposive sampling with 210 observations. The research is analyzed by using regression analysis or Moderate Regression Analysis (MRA). The results show that institutional ownership, profitability and firm size has effect on cash holding. The interaction test results indicate that firm size strengthen the effect of relationship between institutional ownership and cash holding and firm size strengthen the effect of relationship between profitability and cash holding.